2015
DOI: 10.1007/s00428-015-1811-y
|View full text |Cite
|
Sign up to set email alerts
|

Tumor infiltration pattern into the surrounding tissue has prognostic significance in advanced gastric cancer

Abstract: Gastric cancer can be classified into three subgroups according to pattern of tumor infiltration into the surrounding tissue: INFa (expanding growth and a distinct border with the surrounding tissue), INFc (infiltrating growth and an indistinct border with the surrounding tissue), and INFb (in-between a and c). How the tumor infiltration pattern (INF) relates to prognosis and type of recurrence in advanced gastric cancer has not been sufficiently explored. We examined 805 consecutive advanced gastric adenocarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 17 publications
1
15
2
Order By: Relevance
“…INF can be easily determined using only hematoxylin and eosin‐stained sections . However, there have been a few recent studies focusing on the clinical significance of INF in gastric cancer . In the present study, we revalidated the impact of pathological INF on prognosis and recurrence patterns after curative gastrectomy in patients with stage II/III gastric cancer using a large multicenter dataset.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…INF can be easily determined using only hematoxylin and eosin‐stained sections . However, there have been a few recent studies focusing on the clinical significance of INF in gastric cancer . In the present study, we revalidated the impact of pathological INF on prognosis and recurrence patterns after curative gastrectomy in patients with stage II/III gastric cancer using a large multicenter dataset.…”
Section: Discussioncontrasting
confidence: 67%
“…Our findings suggest that INF‐c type gastric cancer tends to grow out of the stomach wall directly by skipping the lymphatic and blood vascular systems, and that INF‐a/b type gastric cancer causes lymphatic involvement and vascular invasion in parallel with growth outside the stomach wall. It has been reported that INF‐c is closely linked to other risk factors for peritoneal metastasis such as Borrmann type 4 tumors, poorly differentiated tumors, and serosal invasion . However, our multivariate analysis revealed that INF‐c was an independent risk factor for peritoneal recurrences.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…This correlates well with the absence of corresponding markers of cytotoxicity, such as perforin and granzyme B. We are prone to believe that this immunosuppressive activity is performed by SRC cells through the selective release of cytokines, which by a paracrine action inhibit the recruitment of T-killer or N-killer lymphocytes, potentially active against the neoplastic elements [7]. This equally takes place in the lymphatic structures of the gastric wall and of the metastatic lymph nodes.…”
Section: Resultssupporting
confidence: 54%
“…Song et al reported that this pattern type was associated with the poorer prognosis in patients with T3 gastric cancer (17). Saito et al reported that lymph node involvement, but not the pattern type, is a prognostic factor in T3 gastric cancer (18). The report by Soga et al is the only recent study of the horizontal width of tumor invasion into the subserosal layer in T3 gastric cancer (11).…”
Section: Discussionmentioning
confidence: 99%